A comparative study of different nanoclay-reinforced cellulose nanofibril biocomposites with enhanced thermal and mechanical properties. Issue 4 (3rd April 2018) - Yong, Cheng; Mei, Changtong; Guan, Mingjie; Wu, Qinglin; Han, Jingquan; Sun, Xiuxuan
Abstract: The objective of this research was to comprehensively compare the effects of nanoclay bentonite (BT), halloysite nanotubes (HNTs) and sulfuric acid-etched halloysite nanotubes on the surface wettability, morphological, mechanical and thermal properties of cellulose nanofibril (CNF) biocomposites. A simple and environmental safe casting-evaporation method was used to fabricate these samples, which comprised up to 10 wt% of nanoclay. The surface wettability, tensile testing and TG results showed that the biocomposites with BT exhibited greater hydrophobicity, larger modulus and strength and better thermal stability than with HNTs at low content. However, at high content, the biocomposites with HNTs exhibited larger elongation at break. The DMA results indicated that biocomposites with HNTs exhibited better molecular motion restriction than with BT. These results combined with Fourier Transform Infrared (FTIR) also indicated interfacial interactions between CNF matrix and nanoclay. Acid treatment would help promote the interfacial interactions between HNTs and CNFs, resulting in enhanced mechanical and thermal properties. This comparative study will help in the choice of appropriate nanoclay for use in functional biomaterials in industrial production applications. Abstract :